Emotional Labor: Scale Development and Validation in the Chinese Context - Yang, Chunjiang; Chen, Yashuo; Zhao, Xinyuan (Frontiers in Psychology, 2019)
Based on the specific cultural context to add greater theoretical precision to emotional labor, we developed the Chinese version scale of emotional labor. For a comprehensive construct development and validation of the new scale, we carried out five studies. First, we used grounded theory methodologies, performed analysis of data from field observations of 15 frontline employees through insider’s angle (Study1) and in-depth interviews with 35 employees (Study 2), and preliminarily glimpsed the main content of emotional labor in China. Second, combined with existing literature and open-ended questionnaires with 110 employees (Study 3), we identified four dimensions labeled as surface acting, deep acting, expression of naturally felt emotions and emotion termination and established the initial items. Third, Study 4 with 166 service workers from China was performed to demonstrate the validity, reliability, and acceptable psychometric properties of the scale and thus formed the formal scale. Finally, multi-wave data with 403 Chinese samples (Study 5) were collected for validating the formal scale. Future researchers can employ this validated scale to investigate emotional labor in Chinese service settings. We expect the emotional labor phenomena in the Chinese context can add valuable and novel insight into the stock of emotional labor knowledge in numerous geographical and cultural contexts.